Repeated ambulatory monitoring reveals an evening rise in blood pressure in a Japanese population - Murakami, Shougo (J Clin Hypertens (Greenwich), 2019)
Recent studies have revealed 2 peaks in the onset of cardiovascular events, 1 in the morning and another in the evening. We evaluated whether blood pressure (BP) also rises in the morning/evening and identified the determinants of evening BP rise using 24‐hour ambulatory BP monitoring for 7 consecutive days. We identified 2 BP peaks, 1 in the morning (0‐3 hours after waking) and 1 in the evening (9‐12 hours after waking). Subjects were subclassified according to the extent of evening BP rise: those in the top quartile (≥6.45 mm Hg, n = 34; ER group) vs all others. After adjustment for age, sex, and 24‐hour systolic BP, evening BP rise was associated with the use of antihypertensive medications [odds ratio (OR), 3.57; 95% confidence interval (CI), 1.46‐8.74; P = .01] and estimated glomerular filtration rate (OR, 0.96; 95% CI, 0.93‐0.99; P = .04), confirming its association with antihypertensive medication use and renal dysfunction.